2022
DOI: 10.1111/1471-0528.17326
|View full text |Cite
|
Sign up to set email alerts
|

Who really benefits from intraperitoneal chemotherapy for advanced ovarian cancer? A treatment‐free survival analysis of the AICE trial

Abstract: Objective To investigate whether peritoneal disease extent can predict the survival benefit of intraperitoneal/intravenous (IP/IV) chemotherapy in ovarian cancer. Design A treatment‐free survival (TFS) analysis. Setting Five‐centre trial. Population An extended follow‐up of the Additional Intraperitoneal Cisplatin and Etoposide in ovarian cancer (AICE) trial (NCT01669226), with data cut‐off on 27 August 2020. Patients were categorised into subgroups with high tumour burden (HTB) and low tumour burden (LTB). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…In the current study, the overall median PCI was 22, with 25 patients (75.8%) having a PCI >17. It represents a population with a relatively high tumor burden according to previous studies, in which patients with a PCI >10 or 17 were classified into the group with a high tumor burden [ 11 12 ]. Similarly, it has been reported that patients with lesser omental involvement had a higher PCI than those without involvement (median PCI, 23 vs. 8) [ 13 ].…”
Section: Discussionsupporting
confidence: 85%
“…In the current study, the overall median PCI was 22, with 25 patients (75.8%) having a PCI >17. It represents a population with a relatively high tumor burden according to previous studies, in which patients with a PCI >10 or 17 were classified into the group with a high tumor burden [ 11 12 ]. Similarly, it has been reported that patients with lesser omental involvement had a higher PCI than those without involvement (median PCI, 23 vs. 8) [ 13 ].…”
Section: Discussionsupporting
confidence: 85%
“…In China, cisplatin is most commonly used for IP chemotherapy, and the treatment cost is covered by the China National Medical Insurance (CNMI). However, acceptance of IP chemotherapy remains limited because of complications associated with catheter use and significant toxicity [ 50 ]. Additionally, catheters have limited availability in China, and they are not covered by CNMI.…”
Section: Intraperitoneal Chemotherapymentioning
confidence: 99%